Hong Kong Women Project a Larger Body When Speaking to Attractive Men - Lee, Albert; Ng, Eva (Frontiers in Psychology, 2022)
In this pilot study we investigated the vocal strategies of Cantonese women when addressing an attractive vs. unattractive male. We recruited 19 young female native speakers of Hong Kong Cantonese who completed an attractiveness rating task, followed by a speech production task where they were presented a subset of the same faces. By comparing the rating results and corresponding acoustic data of the facial stimuli, we found that when young Cantonese women spoke to an attractive male, they were less breathy, lower in pitch, and with denser formants, all of which are considered to project a larger body. Participants who were more satisfied with their own height used these vocal strategies more actively. These results are discussed in terms of the body size projection principle.